Reduction of Methane Slip Emissions from a Medium Speed Dual Fuel Engine - Suokko, Henrik (My University, 2024)
As climate change remains an important global challenge, reducing emissions has become a top priority in seeking sustainable solutions within the marine industry. While natural gas is often considered a cleaner alternative to marine gas oil because of its lower (NOx) emissions, its high level of methane poses a significant challenge. Unburned methane, released as methane slip that has a high greenhouse gas impact, undermines the environmental benefits of natural gas. This thesis addresses the critical need to mitigate methane slip in the marine industry particularly as new regulations on methane emissions are to be implemented in the upcoming years. This thesis aims to identify and evaluate methods to effectively reduce methane slip in a medium-speed dual fuel engine by Wärtsilä (W34DF). The study was conducted through a literature review of previous research regarding uHC mitigation methods in dual fuel engines, as well as simulations of the W34DF engine using GT-POWER software. A single-cylinder simulation model was developed based on the geometry of the W34DF engine and validated against experimental data from W34DF engine tests. Additionally, a previously developed uHC model by Malfi et al. (2021) was implemented into the single-cylinder model and validated against experimental data. After validating the model, simulations to test different piston geometries as well as valve timings were conducted. The simulation results were compared with previous research, demonstrating the model’s accuracy and reliability. The simulation results indicated that methane slip in the W34DF engine can be effectively reduced by altering the piston geometries and adjusting the valve overlap period. Based on these results, two different possibilities for piston geometries were suggested: reducing the crevice volume or increasing the top land gap beyond the critical point needed for the flame to penetrate into the crevice. Furthermore, the results suggested that reducing the valve overlap period could lead to a decrease in emissions. Future research on the feasibility of these methods in the form of experimental tests is suggested to validate their practical applicability and assess potential trade-offs.

Ilmastonmuutoksen jatkuessa merkittävänä maailmanlaajuisena haasteena, päästöjen vähentämisestä on tullut keskeinen tavoite kestävien ratkaisujen kehittämisessä merenkulkualalla. Vaikka maakaasua pidetään usein ympäristöystävällisempänä vaihtoehtona meridieselöljylle (MGO) sen pienempien typenoksidipäästöjen (NOx) vuoksi, kaasun suuri metaanipitoisuus aiheuttaa merkittäviä haasteita. Ilmaan erittäin saastuttavana metaanipäästönä vapautuva palamaton metaani heikentää maakaasun ympäristöhyötyjä merkittävästi. Tämä diplomityö keskittyy merenkulun metaanipäästöjen vähentämiseen, sillä uusia metaanipäästöjä koskevia säädöksiä on tulossa voimaan lähivuosina. Diplomityön tavoitteena oli tunnistaa ja arvioida menetelmiä, joilla voidaan tehokkaasti vähentää metaanipäästöjä Wärtsilän keskinopeassa W34DF-kaksoispolttoainemoottorissa. Tutkimus sisältää kirjallisuuskatsauksen, jossa käsitellään aiempia tutkimuksia kaksoispolttoainemoottoreiden palamattomien hiilivetyjen (uHC) vähentämismenetelmistä, sekä GT-POWER-ohjelmistolla tehdyistä simuloinneista. Tutkimuksen aikana kehitettiin yksisylinterisen moottorin simulointimalli, joka perustuu W34DF-moottorin geometriaan. Malli validoitiin aiemmin suoritettujen koetulosten avulla. Lisäksi Malfin ja muiden (2021) kehittämä uHC-malli sovitettiin yksisylinteriseen malliin sekä validoitiin perustuen kokeellisiin testituloksiin. Mallin validoinnin jälkeen suoritettiin simuloinnit eri männän geometrioiden ja venttiiliajoitusten tutkimiseksi. Simulointien tuloksia verrattiin aiempiin tutkimuksiin, jotta mallin tarkkuus sekä luotettavuus voitiin todentaa. Tulokset osoittivat, että metaanipäästöjä voidaan vähentää W34DF-moottorissa muuttamalla männän geometriaa ja säätämällä venttiiliajoituksia. Niiden perusteella ehdotettiin kahta erilaista ratkaisua männän geometriaan: männän yläpään ja sylinterinholkin välisen tilavuuden pienentäminen tai sen kasvattaminen niin, että liekkirintama pääsee sinne etenemään. Lisäksi tulokset viittasivat siihen, että venttiilin yhtäaikaisen aukioloajan vähentäminen voisi vähentää metaanipäästöjä. Ehdotettujen toimien soveltuvuutta on seuraavaksi tutkittava kokein, joissa myös ehdotettujen vaihtoehtojen välisiä kompromisseja voidaan arvioida.
Keywords: marine industry; methane; emissions; natural gas; combustion engines; fi=Energiatekniikka|en=Energy Technology|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|en=Degree Programme in Electrical Engineering and Energy Technology|; Energiatekniikka